SARANA PEMBELAJARAN UNTUK MENINGKATKAN HASIL BELAJAR - KOMARA NUR IKHSAN (ACADEMIA: Jurnal Inovasi Riset Akademik, 2022)
Learning facilities and infrastructure are everything that can facilitate and expedite the implementation of a business which can be in the form of objects, in this case learning facilities and infrastructure can be equated with learning facilities. Madrasas seek to facilitate the needs of students such as: Providing a fairly representative classroom, decent desk chairs, textbooks and learning support media such as focus, learning aids. The learning infrastructure in the three MTs is still lacking, especially the insufficient laboratory space so that learning in the laboratory often cannot be carried out perfectly. So that it hinders the learning process which has implications for the difficulty of teachers to develop active and creative learning models. ABSTRAKSarana dan prasarana pembelajaran adalah segala sesuatu yang dapat memudahkan dan memperlancar pelaksanaan suatu usaha yang dapat berupa benda dalam hal ini sarana dan prasarana belajar bisa disamakan dengan fasilitas belajar. Madrasah berupaya memfasilitasi kebutuhan peserta didik seperti : Menyediakan ruang kelas yang cukup representatif, kursi meja yang layak, buku pelajaran dan media pendukung pembelajaran seperti infokus, alat peraga pembelajaran. Sarana prasarana pembelajaran di tiga MTs masih kurang, terutama ruang laboratorium belum memadai sehingga pembelajaran di laboratorium sering tidak bisa dilaksanakan dengan sempurna. Sehingga menghambat  terhadap proses pembelajaran yang berimplikasi kepada sulitnya guru untuk mengembangkan model-model  pembelajaran yang aktif dan kreatif.